Corrigenda: Cytogenetic markers as a tool for characterization of hybrids of Astyanax Baird & Girard, 1854 and Hyphessobrycon Eigenmann, 1907. Comparative Cytogenetics 14(2): 231–242. https://doi.org/10.3897/CompCytogen.v14i2.49513 - Goes, Caio Augusto Gomes [UNESP]; Daniel, Sandro Natal [UNESP]; Piva, Lucas Henrique; Yasui, George Shigueki; Artoni, Roberto Ferreira; Hashimoto, Diogo Teruo [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Pensoft Publishers, 2020)
After the publication of our article, we detected some inconsistencies in figures and figure captions. The nominal species Astyanax altiparanae was recently recognized as a new junior synonym of Astyanax lacustris Lütken, 1875. Thus, we corrected this issue in all figures. Captions of figure 3, 5 and 6 were also incorrect. Corrected figures and captions are as follows: